Comparative study of robotic-assisted single-incision-plus-one port and single-incision laparoscopic choledochal cyst excision - Zhang, Ling; Chen, Shan; Lin, Yang; Wang, Jianbin; Qiu, Xinyi; Li, Lizhi (Frontiers in Pediatrics, 2024)
Objective To compare the efficacy of robotic-assisted single-incision-plus-one-port laparoscopic choledochal cyst excision (R-SILC + 1) and single-incision laparoscopic choledochal cyst (SILC) in treating pediatric choledochal cyst (CDC). Methods We retrospectively analyzed the clinical data from forty-nine patients diagnosed with CDC in our hospital from June 2021 to October 2023. About 23 children underwent R-SILC + 1, and 26 children underwent SILC. Demographic parameters, operative details and postoperative outcomes were studied. Results There were no statistically significant differences in demographic data, postoperative pain scores and postoperative complication rate between the two groups (all p>0.05). Compared with the SILC group, the R-SILC+1 group demonstrated less intraoperative bleeding volume (10.4 ± 3.6 vs. 15.0 ± 3.6 mL, p<0.05), a shorter indwelling time of abdominal drainage tube [5(5,6) vs. 7(5.8,8.3) d, p<0.05], a shorter postoperative fasting time [4(3,4) vs. 6(5,7) d, p<0.05] and a shoter postoperative discharge time [6(6,7) vs. 8(6,11) d, p<0.05]. However, the R-SILC+1 group had a longer operation time [388(295,415) vs. 341(255.8,375.2) min, p<0.05], higher hospitalization cost (7.9 ± 0.4 vs. 3.2 ± 0.3 ten thousand, p<0.05). Conclusion Compared with the SILC group, the R-SILC+1 group demonstrated clear advantages in treating pediatric CDC, but it is associated with a prolonged learning curve and operation time, and high costs. With improvements in physician experience and technological advancements, its potential will be further unleashed.